The Characteristics of Pseudorapidity Distributions of Shower Particles Emitted in Interactions of Nuclei with Nuclear Emulsion at 4.5 A GeV/c: Rapidity variable (مجلة البحوث الأكاديمية, 2025)
The present study is based on the interactions caused by silicon nuclei with emulsion nuclei at 4.5 A GeV/c. The main aim is to study the characteristics of pseudorapidity distributions of shower particles emitted in the interactions. The pseudorapidity distributions of shower particles produced in the interactions was well fitted to the Gaussian distribution. The dependence of the pseudorapidity distributions on the projectile mass have been studied. Also, the dependence of the distributions on the target nuclei (AgBr and CNO) has been studied. The variations of the average of pseudorapidity with the average of shower multiplicity have been investigated. The energy density resulting from the interaction was estimated according to the Bjorken model. It was an insufficient energy density for the phase transition to the QGP state to occur.